Living and Leaving : Housing, Mobility and Welfare in the European Union - Inchauste, Gabriela; Karver, Jonathan; Kim, Yeon Soo; Abdel Jelil, Mohamed (World Bank, Washington, DC, 2018)
The availability and affordability of decent housing has become an important economic and social concern in the European Union (EU), as housing price increases in metropolitan regions have often outpaced wage increases. Housing is at the heart of growing economic divides in Europe. This is because productivity growth, which comes with higher wages and better jobs, is concentrated in cities and industrial clusters. Housing is unaffordable in metropolitan centers because the construction of new homes has not kept up with demand, reducing the standard of living of low-income households, and dissuading workers from moving to the most productive regions. While policy incentives have favored homeowners since the 1970s, less attention and resources have been devoted to easing the potential barriers and market restrictions that would allow housing supply to respond to increases in demand. Across EU member states, policymakers should focus on ensuring that land use, rental and other regulations are consistent with incentives to spur residential construction. The report highlights three key recommendations for EU policymakers: earmark unused public land for housing development and speed up approval processes; invest in greenfield projects with improved transportation links from suburban areas, to ensure cities cast a wider economic net; and create public registries to improve transparency of house sale prices to help greater competition between areas.